Long-Lasting Alterations in Membrane Properties, K+ Currents, and Glutamatergic Synaptic Currents of Nucleus Accumbens Medium Spiny Neurons in a Rat Model of Alcohol Dependence - Spigelman, Igor; Marty, Vincent N. (Frontiers in Neuroscience, 2012)
Chronic alcohol exposure causes marked changes in reinforcement mechanisms and motivational state that are thought to contribute to the development of cravings and relapse during protracted withdrawal. The nucleus accumbens (NAcc) is a key structure of the mesolimbic dopaminergic reward system. Although the NAcc plays an important role in mediating alcohol-seeking behaviors, little is known about the molecular mechanisms underlying alcohol-induced neuroadaptive changes in NAcc function. The aim of this study was to investigate the effects of chronic intermittent ethanol (CIE) treatment, a rat model of alcohol withdrawal and dependence, on intrinsic electrical membrane properties and glutamatergic synaptic transmission of medium spiny neurons (MSNs) in the NAcc core during protracted withdrawal. We show that CIE treatment followed by prolonged withdrawal increased the inward rectification of MSNs observed at hyperpolarized potentials. In addition, MSNs from CIE-treated animals displayed a lower input resistance, faster action potentials (APs) and larger fast afterhyperpolarizations (fAHPs) than MSNs from vehicle-treated animals, all suggestive of increases in K+-channel conductances. Significant increases in the Cs+-sensitive inwardly-rectifying K+-current accounted for the increased input resistance, while increases in the A-type K+-current accounted for the faster APs and increased fAHPs in MSNs from CIE rats. We also show that the amplitude and the conductance of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR)-mediated mEPSCs were enhanced in CIE-treated animals due to an increase in a small fraction of functional postsynaptic GluA2-lacking AMPARs. These long-lasting modifications of excitability and excitatory synaptic receptor function of MSNs in the NAcc core could play a critical role in the neuroadaptive changes underlying alcohol withdrawal and dependence.